PENERAPAN MEDIA PROMOSI UNTUK MENDUKUNG SEKTOR USAHA WISATA DESA LALIKO KABUPATEN POLEWALI MANDAR - Basri; Irmayani, Naim; Wahab, Masyitah; Akmal, Muh.; Ramar, Aldila (Universitas Mataram, 2024)
Laliko Village has great tourism potential with its natural beauty and cultural wealth. This can be seen from the potential of mangrove forests and beautiful beach charm. However, less than optimal promotion hinders the development of the tourism sector. For this reason, technological intervention is carried out through the development of the Augmented Reality (AR) application “Visit Laliko” and the visitlaliko.com website. The purpose of this activity is to increase tourist attraction and present complete and interactive information. In addition, the group empowerment approach ensures this program also aims to provide an increase in the ability of tourism managers to use technology-based promotional features. Activity methods include planning, application development, partner training, and implementation of promotional technology. Training is provided to partners to operate AR technology and manage website content. The approach used was a group-based participatory model. The results of the activity showed an increase in partners' knowledge and ability to use technology, with an average increase in ability of 50%. The AR application and website provide complete information about tourist destinations, making it easier for visitors to plan visits. Integration with Google Analytics allows real-time traffic monitoring, helping partners with promotional strategies. In addition, the results of the activities showed an impact on the development of tourism economic businesses with an increase in visitors or tourists by 100% since the program intervention until the initial activity reporting. The technology intervention successfully improved Laliko Village's tourism promotion, making it more attractive and accessible to tourists. This also has an impact on increasing the income of the target community around the tour with the presence of tourist visitors.